(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the emergence of geoeconomics, its theoretical foundations, and its role in contemporary international relations. Following the end of the Cold War, interstate competition increasingly shifted from military means to economic instruments, enhancing the significance of geoeconomic approaches. The study discusses various definitions of geoeconomics and analyzes major theoretical perspectives, including neo-imperialism, neo-mercantilism, world-systems theory, and resource wars. Furthermore, the article highlights the strategic importance of integrating geopolitical and geoeconomic instruments in advancing national interests and strengthening states’ positions in the global arena.